Urgensi Pengaturan Penyelenggaraan Kearsipan Protokol Notaris Untuk Mewujudkan Kepastian Hukum Bagi Notaris - Natalia, Kadek Pingkan; Wiryawan, I Wayan (Acta Comitas : Jurnal Hukum Kenotariatan, 2023)
Writing that lead to get out the importance arrangements regarding the administration of notary protocol filings an image of legal protection by notaries regarding exercising their authority regarding notary protocol storage.  With normative legal research along with statutory approaches through Law Number 2 of 2014 concerning amendments to Law Number 30 of 2004 concerning the Position of Notary and Law Number 43 of 2009 concerning Archives, it was got there was a legal void  regarding the administration of notary protocol filings. Sources of legal material were obtained from literature studies to be further analyzed using deductive logic and resulted a study that the authority a notary in keeping a notary's protocol is regulated in Article 16 paragraph (1) letter b and Article 63 paragraph (4) of the Law on Changes in the Notary's Position, but regulations are required for storing it. Specifically regarding the administration of archives consisting of policies on archives;  management of archives;  and archive management in this case namely the notary protocol, in order to exercise this authority the notary gets legal protection. Meanwhile, neither the Notary's Change of Position Law nor the Archives Law regulate this matter, so it is necessary to establish rules regarding the administration of notary protocol filings in order to create legal certainty for notaries.